Oral surgery simulated teaching; 3D model printing. (21st June 2016) - Shepherd, S.; Macluskey, M.; Napier, A.; Jackson, R.
Abstract: Aim: The aim of this study was to present the development of a cost effective, inexpensive and anatomically accurate model for the teaching of hard tissue oral surgery using three‐dimensional printing technology. Material and methods: Scan data of a dentate human mandible was digitally manipulated and combined with phantom head baseplate data. The resultant three‐dimensional printing of the conglomerate file provided an anatomically accurate plastic model for teaching. Three clinicians with extensive undergraduate oral surgery teaching experience evaluated the resource. Results and conclusion: Initial comments suggest that the printed mandible provides realistic feel, feedback and bone removal experience satisfactory for undergraduate teaching. The authors present a relatively easy, malleable and inexpensive alternative approach for the development and local construction of oral surgery teaching resources.